Aplicação das redes neurais artificiais do tipo perceptron na estimativa de recalques em estacas - Araújo, Carla Beatriz Costa de (2015)
Use of artificial neural networks (ANN) in the estimation of settlements in foundations deep has proven an effective tool. The work of Amancio (2013) and Silveira (2014), the use of RNA showed good results for predicting settlements in continuous stakes propellers, metal piles driven and bored piles. However, some modeled stakes had far behavior of real results, where modeling results indicate sharp increases in stiffness soil-cutting system. In this research, it developed a model with a neural network of the multilayer perceptron to improve the performance of the models Amâncio (2013) and Silveira (2014). To development work initially polls results of analyzes were made Percussion SPT and static load tests of 199 stakes used at work presented by Silveira (2014), making up an assessment of the consistency of the information, in order to have a more heterogeneous and the representative assembly. After conducting changes, has come up with a set with 141 stakes, totaling 1,320 examples of the type entrance exit. Were defined as model input variables: the type of pile, the length of the pile, the pile diameter, the number of representative values ​​when NSPT Over stake stem (called NF), the NSPT on the edge of the pile, depth of the layer the influence of load relative to the cutting edge, the factor representative of the soil layers clay, the representative factor of silty soil layers, the representative factor of the layers sandy soil and the applied load. Four different ways of calculation have been studied in NF input variable, which are: sum, average, weighted sum and weighted average. With input variables presented were worked models where the output variable was the repression of deep foundation. The modeling of RNA was made using the QNET program 2000 and were carried out training and validation of different architectures. The model had better performance showed correlation coefficient between the actual settlements and settlements modeled in the training of 0.99 and 0.98 in the validation. The results proved to be better than those of Amancio (2013) and Silveira (2014), which in the validation phase, They showed correlations of 0.89 and 0.94 respectively. The final model of this work has an architecture comprised of 10 nodes in the input layer, 34 neurons distributed throughout four hidden layers, and one neuron in the output layer (A: 10-15-9-7-3-1) using to calculate the average number of NSPT representative values ​​along the cutting shaft